DMS2015-37: Surveillance system with SIS controller for incident handling using a situation-based Recommendations Handbook. (December 2015) - Jungert, Erland; Chang, S.-K.
Abstract: Protection of critical infrastructures involves handling of incidents that may range from serious to quite harmless events. Such systems require means for surveillance that involves a type of sensor system that may identify entities that behave in an unusual way. However, this is not sufficient as means for determination of entities that seemingly are behaving in a normal way but whose activities somehow relate to the first category, must be determined. Means for the support of the operators must also be available by the surveillance system. In this work, an approach to a surveillance system with a Slow Intelligence systems controller for incident handling using a situation-based recommendations Handbook, is proposed and discussed.